A theoretical essay on the influences of social science paradigms on organizational decisions for sustainability - Maia, Andrei Giovani; Zucatto, Luiz Carlos; Ferreira, Elaine; Neto, José de Pietro; Silva, Geferson Gustavo Wagner Mota da (Seven Editora, 2023)
In a market economy, organizational decisions determine the fate of markets, societies, and nations. The constant challenges and the emergence of socio-environmental problems stimulate societies and organizations to seek a new paradigm as a disruptive worldview model that enables viable solutions and even more effective results, capable of overcoming the previous paradigm. Thus, the predominance of a paradigm tends to influence the evolution of science, organizational decision-making, the adaptation of markets and the advancement of society over time. The development of paradigmatic studies by the social sciences contributed to the classification of different worldviews and specific philosophical aspects that allowed the identification of functionalism/positivism as the dominant paradigm. The economic progress of industrial society was strongly influenced by the functionalist/positivist paradigm, whose philosophical bases are based on Cartesian rational thought directed to the objectives of maximizing economic results. However, given its objectivist and fragmentary bias, this dominant paradigm has serious limitations in disregarding other aspects or challenges such as socio-environmental ones. Currently, recognizing the limitations of the functionalist/positivist paradigm, both science and organizations seek to find models that better meet market demands in a more integrated, systemic and interpretative way to the various socio-environmental dimensions, aspects and challenges, pointing to a paradigmatic transition towards sustainability. Originating from the first author's doctoral thesis, this theoretical essay aimed to reflect on the possible influences of social science paradigms on organizational decisions for sustainability. This study used the paradigmatic classification of Burrell and Morgan (1979) to carry out some reflections on paradigms of the social sciences, organizational decision-making and sustainability. The study resulted in a typology that allows the classification of organizational decisions into simple and complex based on a set of criteria analyzed in the paradigmatic, methodological and theoretical perspective. DOI:https://doi.org/10.56238/sevened2023.006-040